Financial position and Credit Rating of Companies in circular Economy in Serbia - Vukadinović, Predrag; Cerović, Slobodan; Matović, Vladimir; Stevanović, Goran (Industrija, 2018)
The circular economy concept is increasingly gaining in importance. The world’s most developed economies pay more and more attention to this concept. The European Union adopted a special document to affirm the concept. In Serbia, this concept is in its early stages, but is being practically (production) and institutionally actuated. This paper analyses a sample of six companies engaged in different production options in the area of circular economy. The aim of the paper is to analyse the perspective of a new concept in Serbian economy, through assessment of the financial position and credit rating of these companies by applying Altman’s Zʼ and Z”-adjusted score model. The findings in the paper showed that the companies which had been subject to this analysis have such financial position and credit rating that make assessment of their future optimistic. In the light of that, there is a prospect for the development of circular economy concept in Serbia.
Keywords: Z-score zone; Economy; Credit rating; Credit